2013
DOI: 10.1111/cas.12188
|View full text |Cite
|
Sign up to set email alerts
|

Tumor associated macrophage expressing CD204 is associated with tumor aggressiveness of esophageal squamous cell carcinoma

Abstract: Tumor associated macrophages (TAMs) are the most abundant cancer stromal cells educated by tumor microenvironment to acquire trophic functions facilitating angiogenesis, matrix breakdown and cancer cell motility. Tumor associated macrophages have anti-inflammatory properties or "alternatively" activated (M2) phenotype expressing CD204 and ⁄ or CD163. To know the role of TAMs in the growth and progression of esophageal squamous cell carcinomas (ESCCs), we calculated intratumoral CD204, CD163 or CD68 expressing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
169
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 165 publications
(183 citation statements)
references
References 33 publications
12
169
0
2
Order By: Relevance
“…15 These observations suggested to us that TAMs, mainly expressing CD204, may contribute to the progression of ESCCs whose tumor microenvironment might induce the specific differentiation of macrophages recruited from circulating bone marrow-derived peripheral blood monocytes (PBMos). To test our hypothesis, in the present study we exposed PBMo-derived macrophages from healthy volunteers to TECM and observed the cell's acquisition of TAM-like characteristics.…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…15 These observations suggested to us that TAMs, mainly expressing CD204, may contribute to the progression of ESCCs whose tumor microenvironment might induce the specific differentiation of macrophages recruited from circulating bone marrow-derived peripheral blood monocytes (PBMos). To test our hypothesis, in the present study we exposed PBMo-derived macrophages from healthy volunteers to TECM and observed the cell's acquisition of TAM-like characteristics.…”
mentioning
confidence: 87%
“…17,18 Immunohistochemistry Immunohistochemistry was performed with labeled streptavidin biotinylated antibody method as previously described. 15 Specific rabbit polyclonal antibody against growth differentiation factor 15 (GDF15) (HPA011191, 1:50; Sigma-Aldrich, Munich, Germany), specific mouse monoclonal antibodies against CD68 (Kp-1, 1:100; DakoCytomation, Glostrup, Denmark), CD163 (10D6, 1:100; Novocastra, Newcastle upon Tyne, UK), and CD204 (SRA-E5, 1:50; Trans Genic, Kobe, Japan) were used for the primary reaction. For the subsequent reaction, we used labeled streptavidin biotin kit (DakoCytomation).…”
Section: Macrophage Culturesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, elevated IL4, a marker for M2 tumorassociated macrophages (24), is observed in the plasma of human esophageal SCC patients (25). This macrophage subtype is associated with a more aggressive form of esophageal SCC in humans (26). Because M2 macrophages are generally anti-inflammatory (20), higher numbers in esophageal tissue may inhibit the activity of other killer immune cells, thus preventing immune cell-mediated tumor cell destruction (27).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in the expression of these cytokines in the plasma and esophagus at the end of the 35-week bioassay were then confirmed using a smaller subset of markers. Cytokine expression was then related to the presence of specific innate immune cells within the esophagus, including macrophages, neutrophils, and natural killer (NK) cells, all of which have been shown to be associated with esophageal SCC progression in humans (26,(31)(32)(33).…”
Section: Introductionmentioning
confidence: 99%